(untitled) (Vietnam Journal of Community Medicine, 2022)
A cross-sectional descriptive study was conducted on 270 patients with type 2 diabetes undergoing outpatient treatment at Hospital 105, in which the rate of reaching the treatment goal was very low: 31.5% and 71.7% had with hypertension. Objectives: (1) describe the rate of adherence to treatment and (2) analyze some factors related to treatment adherence. The results showed that the percentage of patients who adhered to the drug regimen was 81.5%, the follow-up regimen was 48.2%, the compliance rate to the physical activity regimen was 61.1%, and the compliance regimen was followed. nutrition is 32.2%, adherence to home blood sugar control regimen is 14.1%. The proportion of patients with anxiety is 26.7%. There was a statistically significant relationship between counseling activities of medical staff and the rate of medication adherence and follow-up (p<0.05). The results showed that the rate of adherence to physical activity was higher in the anxiety group than in the non-anxiety group (72.2% vs 57.1%, p < 0.001), in contrast, adherence to the medication regimen and rate The follow-up rate of the group with anxiety was 8.3% compared with that of the group without anxiety was 53.5% (p<0.001). The content of medical staff’s advice that patients can follow only accounts for 13.3%. Conclusion: Poor blood sugar control results may be due to poor adherence to treatment. Poor treatment adherence is related to the poor quality of medical staff’s advice. Anxiety had a negative effect on medication adherence and follow-up visits, but a positive effect on physical performance.